Cost-effectiveness of care for people with psychosis in the community and psychiatric hospitals in the Czech Republic: an economic analysis - Winkler, Petr; Koeser, Leonardo; Kondrátová, Lucie; Broulíková, Hana Marie; Páv, Marek; Kališová, Lucie; Barrett, Barbara; McCrone, Paul (The Lancet. Psychiatry, 2018)
BACKGROUND: The absence of economic evidence hinders current reforms of hospital-based mental health systems in central and eastern Europe. We aimed to assess the cost-effectiveness of discharge to community care for people with chronic psychoses compared with care in psychiatric hospitals in the Czech Republic. METHODS: We did a prospective study of people aged 18-64 years with chronic psychotic disorders in the Czech Republic who had been discharged into community services or were receiving inpatient psychiatric care for at least 3 months at baseline. We measured health-related quality of life with the EuroQol five-dimension five-level questionnaire. Adjusting for baseline differences between the two groups, we assessed differences in societal costs in 2016 and quality-adjusted life-years (QALYs) during a 12-month follow-up, which we then used to estimate the incremental cost-effectiveness ratio (ICER). We did multiple sensitivity analyses to assess the robustness of our results. FINDINGS: In our baseline case scenario, we included 115 patients who were either community service users (n=35) or inpatients (n=80) at baseline. The two groups were similar in terms of baseline characteristics. The annual QALY was 0·77 in patients receiving community care at baseline compared with 0·80 in patients in hospital at baseline (difference 0·03, 95% CI -0·04 to 0·10), but the costs of discharge to the community were €8503 compared with €16 425 for no discharge (difference €7922, 95% CI 4497-11 346), such that the ICER reached more than €250 000 per QALY. This ICER is substantially higher than levels that are conventionally considered to be cost-effective and the estimated probability that discharge to the community was cost-effective was very high (≥97%). None of the sensitivity analyses changed these results qualitatively. INTERPRETATION: This study provides economic evidence for deinstitutionalisation by showing that discharge to community care is cost-effective compared with care in psychiatric hospitals in the Czech Republic. These findings add to the human rights and clinical-based arguments for mental health-care reforms in central and eastern Europe. FUNDING: Ministry of Education, Youth and Sports of the Czech Republic; EEA and Norway Grants.
Keywords: dospělí; Quality-Adjusted Life Years; služby v oblasti duševního zdraví komunity; Female; Adult; mladý dospělý; ženské pohlaví; kvalitativně upravené roky života; lidé; analýza nákladů a výnosů; psychotické poruchy; ústavy pro duševně nemocné; prospektivní studie; Male; Prospective Studies; Czech Republic; Young Adult; Psychotic Disorders; Hospitals, Psychiatric; Community Mental Health Services; Česká republika; lidé středního věku; mužské pohlaví; Middle Aged; Cost-Benefit Analysis; Humans